Efektivitas Pelaksanaan Peraturan Bupati Nomor 12 Tahun 2018 Dalam Program Terpadu Itsbat Nikah Di Kabupaten Pemalang) - maulana, zidan (Al-Hukkam: Journal of Islamic Family Law, 2022)
This study examines the Regent's Regulation Number 12 of 2018 concerning the Acceleration of Increasing the Coverage of Birth Certificate Owners and Death Certificates through the Integrated Marriage Certificate Program. The aim is to determine the effectiveness of the implementation of the integrated marriage itsbat program which is carried out in the context of the validity and accuracy of population data. By using the theory of legal effectiveness developed according to Soerjono Soekanto, the researchers tried to observe the implementation of the integrated marriage marriage certificate program carried out by the Pemalang Regency government which has been running 2 times after the issuance of Regent Regulation Number 12 of 2018. This study found that the program could not be said to be effective because several factors have not gone well, because it turns out that there are still many people who have not registered their marriages, the legal consequences for couples who participate in the program are to get administrative documents quickly and free of charge such as marriage books, birth certificates, and family cards. Meanwhile, the legal consequences of not participating in the program for couples who have not registered their marriages are not having legal guarantees for their marriage and wasting the opportunity for itsbat marriage which has been given by the government quickly and free of charge, because if itsbat is independent it will cost quite a lot and will take the process. trial for a long time.